Quality Assessment of Various Bottled Water Marketed in Algeria: Health-Related Effects - Wahiba Bencheikh*1, 2,3 and .4; Zhor Hattab; Yamina Berredjem; Louis J; Lopes (Annals of R.S.C.B., 2021)
Forty-two different brands between mineral & spring waters were purchased from varied markets in Algeria, they analyzed for their bacteriological quality & chemical major elements. The results showed that all the brands presented good bacteriological quality (Absence of E. coli, Total coliforms, Ps. aerugenosa, enterococci & anaerobic spores). Piper diagram shown that (76.19%) of the samples were classified as Earth Alkaline water, where (80%) of them belong to dominant 𝐻𝐶𝑂3−. By comparing the results with the WHO standards we found that only (16.67%) of the brands are compliant with the standards: Ain Bouglez, Righia, &Besbassa as spring waters, Texanna, El Goléa, Salsabil&Lalla Khadidja as mineral waters, those last two they have not enough TDS to consider them as mineral waters like mentioned in their labels, which confirmed by dendrogram classification. Otherwise, whenthe results comparewith the Algerian standards, all the brand waters turned to be compliant with them except for Arwa. Consumers must be very wary about the consumption of bottled water, especially if they already have health issues because they cannot make a choice only from the labels which are mostly different from the real chemical composition.
Chemical quality of bottled water marketed in Algeria